Smart carboxymethylchitosan hydrogels that have thermo‐ and pH‐responsive properties. Issue 8 (7th October 2014) - Rodkate, Nantharak; Rutnakornpituk, Boonjira; Wichai, Uthai; Ross, Gareth; Rutnakornpituk, Metha
ABSTRACT Thermo‐responsive poly(N‐isopropylacrylamide) (poly(NIPAAm)) and pH‐responsive poly(N, N′‐diethylaminoethyl methacrylate) (poly(DEAEMA)) polymers were grafted to carboxymethylchitosan (CMC) via radical polymerization to form highly water swellable hydrogels with dual responsive properties. Ratios of CMC, NIPAAm to DEAEMA used in the reactions were finely adjusted such that the thermo and pH responsiveness of the hydrogels was retained. Scanning electron microscopy (SEM) indicated the formation of an internal porous structure for the swollen CMC hydrogels upon incorporation of poly(NIPAAm) and poly(DEAEMA). Effect of temperature and pH changes on water swelling properties of the hydrogels was investigated. It was found that the water swelling of the hydrogels was enhanced when the solution pH was under basic conditions (pH 11) or the temperature was below its lower critical solution temperature (LCST). These responsive properties can be used to regulate releasing rate of an entrapped drug from the hydrogels, a model drug, indomethacin was used to demonstrate the release. These smart and nontoxic CMC‐based hydrogels show great potential for use in controlled drug release applications with controllable on‐off switch properties. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41505.